2013
DOI: 10.1007/s13278-013-0105-0
|View full text |Cite
|
Sign up to set email alerts
|

Model for generating artificial social networks having community structures with small-world and scale-free properties

Abstract: Recent interest in complex systems and specially social networks has catalyzed the development of numerous models to help understand these networks. A number of models have been proposed recently where they are either variants of the small-world model, the preferential attachment model or both. Three fundamental properties attributed to identify these complex networks are high clustering coefficient, small average path length and the vertex connectivity following power-law distribution. Different models have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 40 publications
1
31
0
Order By: Relevance
“…Several decades later, Watts and Strogatz [16] and Newman and Watts [17] introduced models for generating smallworld networks. Typically, small-world networks have a relatively high clustering coefficient, and the distance between any two vertices scales as the logarithm of the number of vertices [18]. Barabási and Albert observed that degree distributions that follow power laws exist in a variety of networks, including the World Wide Web [19].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Several decades later, Watts and Strogatz [16] and Newman and Watts [17] introduced models for generating smallworld networks. Typically, small-world networks have a relatively high clustering coefficient, and the distance between any two vertices scales as the logarithm of the number of vertices [18]. Barabási and Albert observed that degree distributions that follow power laws exist in a variety of networks, including the World Wide Web [19].…”
Section: Related Workmentioning
confidence: 99%
“…Even though the models described above can explain some of the characteristics of real-world complex networks, the random networks created by these models were lacking in other properties that were observed in real-world complex networks. Therefore, in recent years, other models have been suggested which have additional characteristics [16,18,22]. Thorough reviews on complex networks and complex network evolution models can be found in books by Chung and Lu [24], Newman et al [25], and by Dorogovtsev and Mendes [26].…”
Section: Related Workmentioning
confidence: 99%
“…An exhaustive review of network generation models is out of scope in this text, yet we have tried to cite a wide spectrum of different network generation models. Partial surveys, reports and comparative analysis for different network generation models can be found in [12], [16], [25], [48], [54]- [57]. None of the models to generate networks considersboth demographic and structural attributes during the network generation process at the same time.…”
Section: Related Workmentioning
confidence: 99%
“…For instance, currently investigations need more sophisticated models that include community structures because it changes the network dynamics. A review on this subject is found in [12]. Also, rewiring schemes need to be considered in the investigations because OSNs undergo changes in their links.…”
Section: Introductionmentioning
confidence: 99%